The Policy Strategy of Rice Straw Utilization of as Feed for Ruminants - Syamsu , Jasmal A; Karim, Hasmida (Asian Journal of Agriculture and Rural Development, 2013)
As it is known that the success of the livestock business associated with feeding management support. Bantaeng District is one district that prioritizes the development of animal husbandry for the welfare of society, also this district has a great potential of agricultural waste. The tools used in the analysis is SWOT-Analysis (Strengths-Weakness-Opportunities-Threats). This matrix combines opportunities and threats which can be match to the strengths and weaknesses to produce an alternative strategy, that is SO strategy, strategy WO, WT strategy, and ST strategy. The final step is making the decision to determine which strategies are feasible alternatives and the best, with Quantitative Strategies Planning Matrix (QSPM) analysis which had previously been given an Attractiveness Score questionnaire. The result of research were the strategies require the provision of rice straw storage in groups on large livestock production centers, increased use of rice straw as a staple feed of cattle, provision of quality rice straw in the dry or drought season, supply and use of straw as animal feed with various methods of delivery and utilization.